Postpartum Home Blood Pressure Monitoring Program: Improving Care for Hypertension During Postpartum after a Hospital Birth. Issue 3 (May 2023) - Hayden-Robinson, Kamilah A.; Deeb, Jessica L.
Abstract: Background and Significance: Hypertensive disorders of pregnancy complicate about 10% of pregnancies and are a leading cause of maternal morbidity and mortality. Purpose: The purpose of this quality improvement project was to evaluate a program to provide a home blood pressure monitor to all postpartum patients who had a hypertensive diagnosis and elevated blood pressure. Methods: The program includes a blood pressure monitor, instructions for its use, education about hypertension, and a guidance grid with standardized blood pressure parameters reviewed prior to discharge from the hospital. Patients are taught about potential adverse outcomes during postpartum. Patients are instructed to follow-up with their care provider based on the parameters. A retrospective medical record review was used to evaluate clinical outcomes. Results: Medical records of 185 patients indicated that 20% ( n = 36) who received the home BP monitor reported one or more mild-to-severe range blood pressure(s) during postpartum. Twenty-eight percent ( n = 52) had outpatient medication adjustments, including decreasing, increasing, starting, and discontinuing medications. Nine percent ( n = 17) of patients returned to the obstetric triage for evaluation. There was patient overlap between those experiencing elevated blood pressures, medication adjustments, and those who returned to hospital for evaluation. Clinical Implications: Ongoing monitoring may improve identification and management of postpartum hypertension and potentially prevent progression to hypertensive-related adverse events. Abstract : In this quality improvement project, patients with a diagnosis of a hypertensive disorder of pregnancy were given a home blood pressure monitor with detailed instructions for use when they were discharged from the hospital after giving birth. Patients monitored their blood pressure at home and reported results to their providers. Timely and appropriate treatment was able to be initiated without a return in-person visit for most patients. The program was well received by patients and providers. Home blood pressure monitoring for new mothers is a feasible method of insuring timely treatment for postpartum hypertension as needed without requiring a trip to the clinic or the hosptial.